Application of the Treynor index in SMEs in the Colombian logistics sector period: 2019-2023 - Daniel Isaac Roque; Andrés Caicedo Carrero; Oscar Humberto Quintero Landinez (Tendencias, 2025)
Introduction: In Colombia, small and medium-sized enterprises (SMEs) operate in a volatile economic environment, which exposes them significantly to systematic risk. Therefore, it is crucial to have tools to evaluate their risk-adjusted financial performance. Objective: To analyze the viability of the Treynor index as a tool for measuring risk compensation in SMEs in the freight forwarding sector. Methodology: through a quantitative approach, financial data from 59 representative companies were examined, using regression models with fixed and random effects, as well as hypothesis testing. Results: the results indicate that, on average, the profitability of these SMEs does not adequately compensate the systematic risk to which they are exposed. However, it was found that the Treynor index can be adapted to the specific characteristics of the logistics sector, suggesting its usefulness as a risk management tool. Conclusion: Moving the use of the Treynor index from market finance to corporate finance constitutes a valid alternative to improve the financial competitiveness of Colombian logistics SMEs, by providing an objective way of evaluating the relationship between risk and profitability.